Response simulation and seismic assessment of highway overcrossings. - Kotsoglou, Anastasios (Earthquake engineering & structural dynamics.)
Interaction of bridge structures with the adjacent embankment fills and pile foundations is generally responsible for response modification of the system to strong ground excitations, to a degree that depends on soil compliance, support conditions, and soil mass mobilized in dynamic response. This paper presents a general modeling and assessment procedure specifically targeted for simulation of the dynamic response of short bridges such as highway overcrossings, where the embankment soil?structure interaction is the most prevalent. From previous studies it has been shown that in this type of interaction, seismic displacement demands are magnified in the critical bridge components such as the central piers. This issue is of particular relevance not only in new design but also in the assessment of the existing infrastructure. Among a wide range of issues relevant to soil?structure interaction, typical highway overcrossings that have flexible abutments supported on earth embankments were investigated extensively in the paper. Simulation procedures are proposed for consideration of bridge-embankment interaction effects in practical analysis of these structures for estimation of their seismic performance. Results are extrapolated after extensive parametric studies and are used to extract ready-to-use, general, and parameterized capacity curves for a wide range of possible material properties and geometric characteristics of the bridge-embankment assembly. Using two instrumented highway overpasses as benchmark examples, the capacity curves estimated using the proposed practical procedures are correlated successfully with the results of explicit incremental dynamic analysis, verifying the applicability of the simple tools developed herein, in seismic assessment of existing short bridges.